Influência da Construção do Castanhão Sobre a Sustentabilidade Agrícola Ambiental e a Qualidade de Vida dos Agricultores no Reassentamento de Curupati Irrigação em Nova Jaguaribara - Ceará - Seidi, Suleimane (2016)
The Dam Castanhão is the most important water equipment Ceará, was built with support from the Federal Government. In addition to being considered the "lungs" of the Integrated Water Resources of Ceará system, including as recipient of the waters of the São Francisco River, making it possible to increase the raw water guarantee, was the most successful weirs construction model in Northeast Brazil. In this sense, the objective of this work is to study the effects generated by the construction of Castanhão on environmental agricultural sustainability and quality of life of resettled farmers settlement Curupati irrigation. Prepare the socioeconomic profile of resettled farmers. Measure the levels of agricultural sustainability of resettled farmers. Check the influence of Castanhão on the population studied quality of life; The study was based on primary data resulting from application of semistructured questionnaire, during the month of October 2015, to collect quantitative and qualitative information, together with the resettled farmers in resettlement Currupati irrigation. In addition to the data, it used the secondary data obtained from the Brazilian Institute of publications of Geography and Statistics (IBGE), Institute for Research and Estratética Economic Ceará (IPECE), Ministry of Agrarian Development (MDA), Universities and other research institutions. The survey results revealed that the Agricultural Environmental Sustainability Index of resettled farmers Curupati Irrigation has average agricultural environmental sustainability and, with a little more effort you can achieve the level of high agricultural sustainability. The Quality of Life Index calculated for before and after the construction of Castanhão shows that farmers resettled obtained a significant gain in the representative values of this index, due to the implementation of the weir. The construction of Castanhão brought to the resettled farmers and their families Curupati Irrigation, proof that it is possible to exert a sustainable agriculture without damaging the environment, quality of life.